A surface-based calibration approach to enable dynamic and accurate quantification of colorimetric assay systems. Issue 37 (2nd September 2021) - Tong, Lin; Hutcheson, Joshua D.
Abstract : A mesh surface that incorporates color saturation, assay time, and standard concentration improves colorimetric assay dynamic range and accuracy. Abstract : Colorimetry is widely used in assay systems for its low-cost, ease-of-use, rapidity, moderate storage requirements and intuitively visible effects. However, the application is limited due to its relatively low sensitivity. Conventional colorimetric calibration methods often use a fixed incubation time that can limit the detection range, system robustness and sensitivity. In this paper, we used color saturation to measure the accumulation of product (correlation coefficient R 2 = 0.9872), and we created a novel "calibration mesh" method based on an expanded sigmoid function to enhance sensitivity. The novel calibration mesh method can be adapted for a wide variety of assay systems to improve robustness and detection range, and provide a dynamic and faster output.